3D Printing in Medicine for Preoperative Surgical Planning: A Review - Tejo-Otero, A.; Buj-Corral, I.; Fenollosa-Artés, F. (Annals of biomedical engineering, 2020)
The aim of this paper is to review the recent evolution of additive manufacturing (AM) within the medical field of preoperative surgical planning. The discussion begins with an overview of the different techniques, pointing out their advantages and disadvantages as well as an in-depth comparison of different characteristics of the printed parts. Then, the state-of-the-art with respect to preoperative surgical planning is presented. On the one hand, different surgical planning prototypes manufactured by several AM technologies are described. On the other hand, materials used for mimicking different living tissues are explored by focusing on the material properties: elastic modulus, hardness, etc . As a result, doctors can practice before performing surgery and thereby reduce the time needed for the operation. The subject of patient education is also introduced. A thorough review of the process that is required to obtain 3D printed surgical planning prototypes, which is based on different stages, is then carried out. Finally, the ethical issues associated with 3D printing in medicine are discussed, along with its future perspectives. Overall, this is important for improving the outcome of the surgery, since doctors will be able to visualize the affected organs and even to practice surgery before performing it.